Challenges in the transition from school to work: research findings on the professional integration of young people with handicaps in Switzerland - Pool Maag, Silvia (Swiss Journal of Educational Research, 2018)
The transition from school to work requires to be able to act in a labour and professional oriented context. The transition appears as a multi complex process, in witch various system variables are interacting and different actors are influencing it by decision making. This creates challenges that show up at the interface between the workplace, the education system and the opportunities for participation of young people. The professional integration can be promoted if the career choice process is supported by targeted matching, when the willingness and ability of the trainers is furthered, when integrative school models are promoted and Supported Education will be used needs-oriented.